Future Directions of Rheumatology Training According to Saudi Vision 2030: Recommendations From a Saudi Experts Meeting - Zaini, Rania (Open Access Rheumatol, 2020)
BACKGROUND: Worldwide research anticipates that a current shortage of rheumatologists will exacerbate over the next decade, whereas the need for arthritis specialists will continue to escalate. Saudi Arabia (SA) also encounters a limited geographical distribution of rheumatologists and rheumatology fellowship training centres. OBJECTIVE: Reporting the Saudi rheumatologists’ advisory meeting conducted in Makkah, SA in January 2020 with the aim to discuss the “Saudi Vision 2030” for rheumatology training programs. MATERIALS AND METHODS: A meeting of Saudi rheumatology experts and consultants was conducted to address the future directions, challenges, and recommendations of rheumatology training. The 10th Rheumatology Practice Symposium was organised by Alzaidi Chair of Research in Rheumatic Diseases (ZCRD), and conducted in Makkah Commerce Chamber, Makkah, SA on January 28, 2020. More than 30 consultants and rheumatology fellows with five Saudi experts in the field of rheumatology assembled to form 10 recommendations that tackle rheumatology training challenges in SA. RESULTS: The meeting recommendations shed light on the clinical practice of rheumatology training in SA; challenges and opportunities in rheumatology fellowship programs; efforts of the Saudi Commission for Health Specialties (SCFHS) to design and implement a competent postgraduate rheumatology training; and challenges with trainers, trainee, and within training centres. CONCLUSION: To address rheumatology challenges in SA, rheumatology consultants and fellows assembled to form 10 recommendations. The recommendations tackled the challenges of rheumatology fellowship programs and the efforts to implement a competent postgraduate rheumatology training. These recommendations are expected to lead us successfully to fulfil our ambition in the “Saudi Vision of 2030”.